2002
DOI: 10.1038/sj.jhh.1001339
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction, angiotensin-converting enzyme inhibitors and calcium antagonists

Abstract: The endothelium plays a crucial role in the pathogenesis of cardiovascular disease. Endothelial function is attenuated by the presence of different well known cardiovascular risk factors. Evaluation of endothelial vasodilator function serve as an index integrating the overall stress imposed by cardiovascular risk factors and reinforce the suggestion that endothelial dysfunction is an early marker of cardiovascular disease that precedes clinical manifestations. Angiotensin-converting enzyme inhibitors have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…In MetS patients, serum adiponectin levels are decreased, while proinflammatory cytokines are elevated [18]. This imbalance in the inflammatory state leads to dysfunction of the endothelial cells, promoting the loss of their vasodilatory, antithrombotic, and antiatherogenic properties [19,20], apparently a widespread biological response in humans [21]. The relationship between inflammation and MetS is supported by several studies [1,18,22], as is the association between increased visceral fat mass and MetS [23].…”
Section: Abdominal Obesity and Adipokine Imbalancementioning
confidence: 91%
“…In MetS patients, serum adiponectin levels are decreased, while proinflammatory cytokines are elevated [18]. This imbalance in the inflammatory state leads to dysfunction of the endothelial cells, promoting the loss of their vasodilatory, antithrombotic, and antiatherogenic properties [19,20], apparently a widespread biological response in humans [21]. The relationship between inflammation and MetS is supported by several studies [1,18,22], as is the association between increased visceral fat mass and MetS [23].…”
Section: Abdominal Obesity and Adipokine Imbalancementioning
confidence: 91%
“…[12][13][14] Major functional consequences of endothelial dysfunction in diabetes are reduced bioavailability of endothelium-derived nitric oxide with impaired endothelial-dependent dilatation in either type of human diabetes. 14 15 Recently, improvement in endothelial function was shown after various treatments such as lipid-lowering drugs, 16 antioxidants, 17 angiotensin-converting enzyme inhibitors, 18 calcium channel blockers 19 and oestrogen replacement. 20 Inhibitors of hydroxymethyl glutaryl coenzyme A (HMG-CoA) reductase (statins) have currently been used extensively to lower serum cholesterol levels with their proved antithrombotic, antiproliferative and anti-inflammatory properties.…”
mentioning
confidence: 99%
“…1 Furthermore, animal and human studies confirm that the beneficial effects of ACEI in reversing endothelial dysfunction. 7 On the other hand, regarding the concerning that the high level of ACE2 expression might facilitate infection with COVID-19, there is no direct evidence shown that ACE2 level is positively correlated with the infection risk. Several studies reported that COVID-19 related mortality was higher in men and the elderly than women and the young, but the level of ACE2 was shown oppositely.…”
Section: Regarding Whether Covid-19 Patients With Hypertension Shouldmentioning
confidence: 99%